2015
DOI: 10.1038/mi.2014.128
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiotic bacteria translocate in progressive SIV infection

Abstract: Infection of gut-resident CD4+ memory T-cells during acute HIV and SIV infection is associated with rapid loss of these cells and damage to the epithelial barrier. Damage to the epithelial barrier allows translocation of microbial products from the intestinal lumen into the body. Immune activation caused by these microbial products has been associated with disease progression. Although microbial translocation has been demonstrated in SIV-infected nonhuman primates, the identity of translocating bacteria has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
149
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(163 citation statements)
references
References 49 publications
(48 reference statements)
12
149
2
Order By: Relevance
“…In this report, we sought to examine the role of events at the interface of the gut mucosa and the systemic immune system to explore which factors influence peripheral CD4 + T-cell reconstitution following effective cART. We and others have previously demonstrated that higher percentages of proinflammatory bacterial taxa including the Proteobacteria/Enterobacteriales were associated with changes in the duodenal GALT T-cell subset proportions and T-cell activation [33, 60]. Similarly, Dillon et al .…”
Section: Discussionmentioning
confidence: 67%
“…In this report, we sought to examine the role of events at the interface of the gut mucosa and the systemic immune system to explore which factors influence peripheral CD4 + T-cell reconstitution following effective cART. We and others have previously demonstrated that higher percentages of proinflammatory bacterial taxa including the Proteobacteria/Enterobacteriales were associated with changes in the duodenal GALT T-cell subset proportions and T-cell activation [33, 60]. Similarly, Dillon et al .…”
Section: Discussionmentioning
confidence: 67%
“…One potential mechanism underlying damage to the epithelial barrier is alterations in the microbial communities of the GI tract. In HIV infection, there is an increased abundance of epithelial-adherent bacteria of the Proteobacteria family [38], and interestingly, it is this increased Proteobacteria that is found to predominantly translocate in SIV infection [39**]. This suggests that interactions between bacteria associated with the mucosa and the epithelium may contribute to MT.…”
Section: Microbial Translocation In Hiv Infectionmentioning
confidence: 99%
“…Antiretroviral therapy (ART) successfully controls systemic HIV replication but immune recovery is variable (Maartens et al, 2014). A hallmark of HIV disease is a rapid and profound depletion of CD4 T cells in the gut-associated lymphoid tissue (Brenchley et al, 2004; Klatt et al, 2008) and increased translocation of microbial products across this compromised epithelial barrier (Brenchley et al, 2006; Klase et al, 2015). HIV infection can also lead to enteropathy characterized by increased gastrointestinal (GI) inflammation, diarrhea and malabsorption (Brenchley, 2013).…”
Section: Introductionmentioning
confidence: 99%